Problematika Pengaturan Batas Usia Pendiri Dalam Pendirian Perseroan Perseorangan - Widiantara, I Wayan Gede Pradnyana; Purwanto, I Wayan Novy (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 1 (2024)DO - 10.24843/JMHU.2024.v13.i01.p10, 2024)
The purpose of writing this article is to determine the setting of the age limit for founders when establishing an Individual Limited Liability Company and to analyze the legal implications of establishing an individual limited liability company by immature founders. Normative legal research methods with statutory approaches and conceptual approaches are used in this study. The results of this study indicate that the age limit for founders when establishing an Individual Limited Liability Company is regulated in Article 6 paragraph (2) PP No. 8 of 2021, which requires that Indonesian citizens be established with the lowest age of 17 (seventeen) years and are legally competent. Meanwhile, according to Article 330 of the Civil Code states that a person is considered mature if he is 21 (twenty one) years old or has (already been) married. Related to the legal implications of the establishment of an Individual Limited Liability Company by an immature founder reviewed based on the Civil Code, it is possible to cancel the legal act of establishing the Individual Limited Liability Company. Provisions of PP No. 8 of 2021, which regulates the age limit for the founder in the establishment of an Individual Limited Liability Company contains a norm conflict with legal norms above, namely the Civil Code, so it is very necessary to make adjustments to the implementing provisions in the establishment of Individual Limited Liability Company in Indonesia in order to create legal certainty in its application. Penulisan artikel ini bertujuan untuk mengetahui pengaturan batas usia pendiri dalam pendirian Perseroan Perorangan, serta untuk menganalisa implikasi yuridis pendirian Perseroan Perorangan oleh pendiri yang belum dewasa. Metode penelitian hukum normatif dengan pendekatan perundang-undangan dan pendekatan konsep dipergunakan dalam penelitian ini. Hasil kajian ini menunjukkan bahwa batas usia pendiri dalam pendirian Perseroan Perorangan mengacu pada pasal 6 ayat (2) PP No. 8 Tahun 2021, yang mensyaratkan didirikan oleh Warga Negara Indonesia dengan usia terendah 17 (tujuh belas) tahun dan cakap hukum. Sedangkan menurut Pasal 330 KUHPerdata menyatakan bahwa dianggap dewasanya seseorang jika sudah berusia 21 (dua puluh satu) tahun atau sudah (pernah) menikah. Terkait implikasi yuridis pendirian Perseroan Perorangan oleh pendiri yang belum dewasa ditinjau berdasarkan KUHPerdata, adalah dapat dibatalkannya perbuatan hukum pendirian Perseroan Perorangan tersebut. Ketentuan PP No. 8 Tahun 2021 yang mengatur batas usia pendiri dalam pendirian Perseroan Perorangan mengandung konflik norma dengan norma hukum peraturan diatasnya yakni KUHPerdata, sehingga sangat perlu dilakukan penyesuaian terhadap ketentuan-ketentuan pelaksanaan dalam pendirian Perseroan Perorangan di Indonesia guna menciptakan kepastian hukum dalam penerapannya.